2019
DOI: 10.1042/bsr20181025
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PSCA gene polymorphisms in modulating gastric cancer risk in the Chinese population

Abstract: Previous studies have identified the prostate stem cell antigen (PSCA) gene rs2294008 C > T and rs2976392 G > A polymorphisms to be associated with the risk of gastric cancer, the results of which are inconsistent. The present study aimed to evaluate the association between the two polymorphisms and the gastric cancer risk in the Chinese population. A hospital-based case–control study was conducted on 549 cases and 592 healthy controls. Odds ratios (ORs) and 95% confidence intervals (CIs) were applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Since PSCA is expressed in the gastric gland isthmus, anatomical factors may influence the location of GC. In this meta-analysis, the effect of PSCA rs2294008 on non-cardia gastric cancer was significantly higher than that of cardia gastric cancer, which was consistent with the results of previous studies (32,37). Similarly, the Lauren classification analysis showed that the disease susceptibility of the diffuse type was higher than that of the intestinal type.…”
Section: Discussionsupporting
confidence: 91%
“…Since PSCA is expressed in the gastric gland isthmus, anatomical factors may influence the location of GC. In this meta-analysis, the effect of PSCA rs2294008 on non-cardia gastric cancer was significantly higher than that of cardia gastric cancer, which was consistent with the results of previous studies (32,37). Similarly, the Lauren classification analysis showed that the disease susceptibility of the diffuse type was higher than that of the intestinal type.…”
Section: Discussionsupporting
confidence: 91%
“…The PSCA polymorphism is associated with high expression of PSCA in cancer patients [ 61 ]. The T allele of PSCA rs2294008 could decrease the transcriptional activity of the PSCA promoter in gastric cell lines [ 62 ]. The rs2976392 G>A and rs2294008 C>T polymorphisms are the most widely studied polymorphisms in the PSCA , and have been proved to be associated with an increased risk of gastric cancer [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on a study, rs2294008CT and rs2294008CT + TT can increase the risk of gastric cancer in the Chinese population (in young people, non-smokers, non-alcoholics, men and non-cardia patients). The possible mechanism of action for this polymorphism is that this variant reduces the transcriptional activity of the PSCA upstream fragment [ 56 , 83 ]. It was found that the rs2294008 T allele resulted in a significant reduction in transcriptional activity of the PSCA promoter in gastric cell lines [ 32 ].…”
Section: Psca Expression and Polymorphisms In Different Cancersmentioning
confidence: 99%
“…The rs2976392G > A variant is also associated with an increased risk of gastric cancer, but its mechanism of action is unclear. This variant has a strong linkage disequilibrium with rs2294008, which could justify its function [ 83 ]. rs2294008 variant is more associated with diffuse-type gastric cancer than intestinal type in Korean and Japanese populations.…”
Section: Psca Expression and Polymorphisms In Different Cancersmentioning
confidence: 99%